1994
DOI: 10.1016/0014-5793(94)00678-4
|View full text |Cite
|
Sign up to set email alerts
|

Binding of retinoids to uteroglobin

Abstract: Uteroglobin, a progesterone-binding secretory protein, was shown to bind retinoic acid and retinol in a non-saturable manner, at least up to concentrations of retinoids of 20 PM. Binding is increased about IO-fold by previous reduction of uteroglobin with 10 mM dithothreitol and it is not affected by previous saturation of the progesterone binding site, suggesting different binding sites for the steroid and the retinoids. The results are discussed in relation to a possible physiological role for this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Thus, in addition to the results shown here, binding of UG to progesterone [1,2] or retinoids [11] is greatly enhanced by treatment with reducing agents. This implies that UG must be in a reduced form to exert these possible functions in physiological conditions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, in addition to the results shown here, binding of UG to progesterone [1,2] or retinoids [11] is greatly enhanced by treatment with reducing agents. This implies that UG must be in a reduced form to exert these possible functions in physiological conditions.…”
Section: Discussionsupporting
confidence: 70%
“…UG inhibits phospholipase A2 in vitro [2] and might also act as an immunosuppressant in avoiding the rejection of the embryo [2]. More recently, UG has been shown to bind retinoids [11]. None of these properties has been conclusively related to a physiological function.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the steroidbinding ability of PSBP, UG/CC10 and msABP [9,10,12,35] might be relevant, if it is demonstrated for the FHG22 protein. However, no homologies have been found to the canonical (but not general) steroid-binding sequence motif [42] in any of these proteins, while it has been found that besides steroids and polychlorinated biphenyls, rabbit UG binds retinoids and probably membrane proteins [21,43] and human CC10 binds calcium [20]. The protein might be secreted both to the saliva and eye secretion and bind different ligands, playing a role similar to the immunomodulatory/protective action described for UG/CC10 in the female genital tract [10,44] and the lungs [31,32].…”
Section: Tissue-specific Expression Of the Fhg22 Mrnamentioning
confidence: 97%
“…Sequence similarities between PSBP and UG [13] and between UG, FdI 1 and msABP ~ have been reported [11,14], while the genes for PSBR UG and FdI 1 show a common structure [15,16,17,18,19]. In addition, it has been described that PSBP and msABP bind steroids [9,12,15], while UG/CC10 also binds other ligands [10,20,21]. However, this group of proteins presents a wide tissue distribution and a complex hormonal regulation [10,11,12,22].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this protein is known by several names, which are primarily derived from the organ or body fluid in which it is detectable or from the type of xenobiotics with which it interacts. Thus, it is called the progesterone-binding protein [8], Clara cell 10 kDa protein [9], urine protein-1 [7], polychlorinated biphenyl-binding protein [10], and retinol-binding protein [11]. Recently, the UG/Clara cell family of proteins has been classified as members of a new superfamily called ''secretoglobins'' [12].…”
mentioning
confidence: 99%